Lonergan and Historiography : The Epistemological Philosophy of History - McPartland, Thomas J., 1945- (Book collections on Project MUSE., 2010)
""A thorough, well-researched, well-informed, elegantly written work. McPartland unfolds in a single volume the implications of Lonergan's foundational studies for philosophy of history. In doing so, he does for Lonergan what Lonergan did not have time to do himself."--Mark D. Morelli, coeditor of The Lonergan Reader" ""A very profound contribution to the contemporary understanding of historiography and its possibilities."--Glenn Hughes, author of Transcendence and History: The Search for Ultimacy from Ancient Societies to Postmodernity" "Although Bernard Lonergan is known primarily for his congnitional theory and theological methodology, he long sought to formulate a modern philosophy of history free of progressive and Marxist biases. Yet he never addressed this in any single work, and his reflections on the subject are scattered in various writings." "In this pioneering work, Thomas McPartland shows how Lonergan's over all philosophical position offers a fresh and comprehensive basis for considering historiography. Taking Lonergan's Philosophy of historical existence into the realm of an epistemological philosophy of history, he demonstrates how the philosopher's approach builds on the actual performance of historians and, as a result, integrates the insights of historical specialists into a framework of functional complementarity."